Identification of Speech Types and Politeness Principles in Speech Discourse of Irma Suryani vs Rocky Gerung on Kompas TV - Nasution, Muhammad Muslim; Izar, Julisah; Yuliana, Yessa (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2024)
This study aimed to describe and explain the types of speech and principles politeness used by Irma Suryani and Rocky Gerung in the Kompas TV program, the method in this study is to use a qualitative descriptive approach. The data source in this study is in the form of direct speech, spoken by Irma Suryani and Rocky Gerung on the Kompas TV program. The data collection technique in this analysis is in the form of a listening method and a note-taking technique. The data analysis technique uses interactive qualitative analysis. After the analysis was carried out, it was concluded that: 1) The types of speech acts used in the speech discourse of Irma Suryani and Rocky Gerung include: assertive speech acts, directive speech acts, expressive speech acts, and declarative speech acts. 2) The principles of politeness used in the speech discourse of Irma Suryani and Rocky Gerung include: the maxim of wisdom, the maxim of appreciation and the maxim of agreement.